The impact of alpha-syntrophin deletion on the changes in tissue structure and extracellular diffusion associated with cell swelling under physiological and pathological conditions - Dmytrenko, Lesia; Cicanic, Michal; Anderova, Miroslava; Vorisek, Ivan; Ottersen, Ole Petter; Sykova, Eva; Vargova, Lydia (PLoS One, 2013)
Aquaporin-4 (AQP4) is the primary cellular water channel in the brain and is abundantly expressed by astrocytes along the blood-brain barrier and brain-cerebrospinal fluid interfaces. Water transport via AQP4 contributes to the activity-dependent volume changes of the extracellular space (ECS), which affect extracellular solute concentrations and neuronal excitability. AQP4 is anchored by α-syntrophin (α-syn), the deletion of which leads to reduced AQP4 levels in perivascular and subpial membranes. We used the real-time iontophoretic method and/or diffusion-weighted magnetic resonance imaging to clarify the impact of α-syn deletion on astrocyte morphology and changes in extracellular diffusion associated with cell swelling in vitro and in vivo. In mice lacking α-syn, we found higher resting values of the apparent diffusion coefficient of water (ADCW) and the extracellular volume fraction (α). No significant differences in tortuosity (λ) or non-specific uptake (k'), were found between α-syn-negative (α-syn -/-) and α-syn-positive (α-syn +/+) mice. The deletion of α-syn resulted in a significantly smaller relative decrease in α observed during elevated K(+) (10 mM) and severe hypotonic stress (-100 mOsmol/l), but not during mild hypotonic stress (-50 mOsmol/l). After the induction of terminal ischemia/anoxia, the final values of ADCW as well as of the ECS volume fraction α indicate milder cell swelling in α-syn -/- in comparison with α-syn +/+ mice. Shortly after terminal ischemia/anoxia induction, the onset of a steep rise in the extracellular potassium concentration and an increase in λ was faster in α-syn -/- mice, but the final values did not differ between α-syn -/- and α-syn +/+ mice. This study reveals that water transport through AQP4 channels enhances and accelerates astrocyte swelling. The substantially altered ECS diffusion parameters will likely affect the movement of neuroactive substances and/or trophic factors, which in turn may modulate the extent of tissue damage and/or drug distribution.
Keywords: Muscle Proteins; Potassium; Male; Mice, Knockout; Aquaporin 4; draslík; Genotype; srdeční zástava; Diffusion; svalové proteiny; Osmotic Pressure; membránové proteiny; Somatosensory Cortex; Astrocytes; ischemie; Membrane Proteins; difuze; mužské pohlaví; Ischemia; genový knockout; Gene Deletion; Heart Arrest; osmotický tlak; myši knockoutované; Animals; Gene Knockout Techniques; extracelulární prostor; ženské pohlaví; Extracellular Space; zvířata; akvaporin 4; Calcium-Binding Proteins; myši; proteiny vázající vápník; delece genu; genotyp; somatosenzorické korové centrum; astrocyty; Female; Mice